Impacto da redução do fósforo suplementar sobre fertilidade, habilidade materna e custos com suplementação mineral em vacas de corte mantidas em Urochloa decumbens: Rogério Magnoli Costa. - - Costa, Rogério Magnoli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brazilian livestock consists of animals raised and finished in tropical pastures, most of them established in medium and low fertility soils. The tropical forages, however, are limited in some nutrients, especially in minerals, which can compromise the results of cattle production. Among the minerals, phosphorus (P) occupies an important position due to its role in animals' metabolism and to its cost, which represents most of the mineral supplements costs, so rendering this input the most expensive for the definition of the production costs of cattle raised in grasslands. Often, the farmers do not follow the ideal techniques for the animal's' mineral supplementation and, besides that, practical observations suggest that not always the animal productivity is related to the mineral supplementation techniques or with the P contents of the supplements. Following the hypothesis that the recommended levels of P can be reduced without damaging the animal productivity, the aim of this trial was to check on the effects of reducing the phosphorus supplementation concentrations (from 4% to 1.8%) in a beef cow herd raised on Urochloa decumbens pastures on the productive and reproductive parameters, as well as on the supplementation costs. The study was conducted on the cerrado biome, from 2011 to 2013. Variables analyzed included pregnancy rate, calving interval, weight of calves at weaning and cost of supplementation. No changes were found for the productive and reproductive performance of the herd. However, there was a significant reduction in the supplementation costs when the herd was supplemented with a mineral mixture containing 1.8% phosphorus
Keywords: Bovino de corte; Pastagens extensivas; Fosforo na nutrição animal; Reprodução animal; Suplementos dieteticos; Minerais na nutrição animal; Custo; Extensive grazing